Management of an unusual cause of life-threatening haemoptysis: a multidisciplinary approach. Issue 5 (20th May 2021) - Pramanik, Kim; Webb, Philip; Hamid, RanaShoaib
Abstract : We present to you a case of life-threatening haemoptysis secondary to non-cystic fibrosis bronchiectasis complicated by bronchial artery pseudoaneurysms. We discuss this patient's emergency medical management using intravenous tranexamic acid, which resulted in successful resuscitation and eventual survival, and evaluate the need for urgent anaesthetic and interventional radiology input in such a case.